APPLICATION OF PHOSPHATE SOLUBILIZING FUNGI FROM ISOLATE ULTISOL PADANG BULAN MEDAN INCREASED GROWTH OF CORN (Zea mays L) - Aisyah Lubis; Nurma Ani; Ahmad Sofian (AGRIUM: Jurnal Ilmu Pertanian, 2016)
Phosphate solubilizing fungi from ultisol acid soil can be used as biological fertilizer to increase corn growth. Field experiment to be done to know effect of Phosphate solublizing fungi (PSF) and anorganic P fertilizer on corn on ultisol. The Randomly Complete Block design used that consist two factors, eg. fungi of PSF and anorganic P fertilizer. Factor fungi of PSF (M) with four levels : M0 = without PSF; M1= PSF from corn  rizhosphere (10 ml/plant hole); M2= PSF from chilli rizhosphere  (10 ml/plant hole) and M3=PSF from banana rizhosphere. (10 ml/plant hole). Second factor was anorganic P fertilizer (P) with three levels: P0= without anorganic P fertilizer; P1= halp of anorganic P fertilizer recomendation dosage and P2= anorganic P fertilizer recomendation dosage. Results showed that application of PSF increased plant  hight of plant hingher than without PSF. Anorganic P fertilizer application increased, hight  of plant hei significant.Application.of anorganik P fertilizer increased stemp diamter very sinificant but not significant on plant heiggth.  Interaction effect PSF with anorganic P  fertilizaer  was not significant on corn growth.. Keyword: anorganic P fertilizer, phosphate solubilizing fungi  and ultisol soil